5SRNAdb: an information resource for 5S ribosomal RNAs. Issue Volume 44:Issue D1(2016) (20th October 2015) - Szymanski, Maciej; Zielezinski, Andrzej; Barciszewski, Jan; Erdmann, Volker A.; Karlowski, Wojciech M.
Abstract: Ribosomal 5S RNA (5S rRNA) is the ubiquitous RNA component found in the large subunit of ribosomes in all known organisms. Due to its small size, abundance and evolutionary conservation 5S rRNA for many years now is used as a model molecule in studies on RNA structure, RNA–protein interactions and molecular phylogeny. 5SRNAdb (http://combio.pl/5srnadb/ ) is the first database that provides a high quality reference set of ribosomal 5S RNAs (5S rRNA) across three domains of life. Here, we give an overview of new developments in the database and associated web tools since 2002, including updates to database content, curation processes and user web interfaces.